2019
DOI: 10.1101/2019.12.16.878553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic representation of taste-related decisions in the gustatory insular cortex of mice

Abstract: SUMMARYResearch over the past decade has established the gustatory insular cortex (GC) as a model for studying how primary sensory cortices integrate multiple sensory, affective and cognitive signals. This integration occurs through time varying patterns of neural activity. Selective silencing of GC activity during specific temporal windows provided evidence for GC’s role in mediating taste palatability and expectation. Recent results also suggest that this area may play a role… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…11 As recent findings elegantly demonstrate, optogenetic activation of aIC PV does not affect chemosensation itself but can disrupt cognitive signals that drive the execution of tasteguided, reward-directed decision making. 48 Thus, activation of aIC PV during CTA retrieval likely represents a memorydependent halt in taste-guided drives toward the CS through the fine-tuning of synaptic activity on aIC-BLA-projecting neurons.…”
Section: Discussionmentioning
confidence: 99%
“…11 As recent findings elegantly demonstrate, optogenetic activation of aIC PV does not affect chemosensation itself but can disrupt cognitive signals that drive the execution of tasteguided, reward-directed decision making. 48 Thus, activation of aIC PV during CTA retrieval likely represents a memorydependent halt in taste-guided drives toward the CS through the fine-tuning of synaptic activity on aIC-BLA-projecting neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach to studying perceptual expectations in headfixed mice was inspired by previous human psychophysical studies (Wright and Fitzgerald, 2004;Best et al, 2007). While head-fixed mice can perform two-alternative forced choice tasks (Sanders and Kepecs, 2012;Burgess et al, 2017;Vincis et al, 2020), we used Go/No-Go task designs which could be learned over the course of one to two weeks, allowing us to layer manipulations of perceptual expectations on top of basic detection or discrimination tasks (Guo et al, 2014;McGinley et al, 2015;Kuchibhotla et al, 2017). As appetitive Go/No-Go behaviors typically result in a bias toward responding (Gomez et al, 2007), the role of baseline response bias and motivational structure introduced by our task designs likely played a role in the expectation-related effects we observed.…”
Section: Discussionmentioning
confidence: 99%
“…This fits with a recent primate neuroimaging study that showed strong activation of this entire region by visual cues indicating reward, as well as reward delivery 20 . Insula has long been known to be strongly connected with the neighboring gustatory cortex 34,35 . Recently, several lines of studies have demonstrated that neurons in the gustatory cortex not only engage the primary processing of gustatory inputs, but also involve multisensory integration 15,16 , as well as higher cognitive functions like decision-making 13,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Insula has long been known to be strongly connected with the neighboring gustatory cortex 34,35 . Recently, several lines of studies have demonstrated that neurons in the gustatory cortex not only engage the primary processing of gustatory inputs, but also involve multisensory integration 15,16 , as well as higher cognitive functions like decision-making 13,35 . This suggests that primate insular cortex and the neighboring gustatory cortex are strongly interconnected and form an interacting distributed network during decision making.…”
Section: Discussionmentioning
confidence: 99%